2005
DOI: 10.1590/s0100-39842005000100014
|View full text |Cite
|
Sign up to set email alerts
|

Fibrodisplasia ossificante progressiva: relato de caso e achados radiográficos

Abstract: Araújo Júnior CR et al. Radiol Bras 2005;38(1):6973 69A expressão fibrodisplasia ossificante progressiva substitui a antigo nome miosite ossificante (6) , por ser a osteogênese ectópica ocorrendo no tecido conjuntivo, podendo afetar músculos, fáscias, ligamentos, tendões e cápsulas articulares.O doente geralmente apresenta ossificação progressiva do tecido conjuntivo, que causa uma limitação crescente da mobilidade osteoarticular, afetando principalmente a coluna vertebral, ombros, quadril e articulações perif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
(11 reference statements)
0
11
0
2
Order By: Relevance
“…17,18 In 1918, Rosenstirn conducted an extensive review of the medical literature, describing 115 cases of FOP. 14,17 The disease was first named myositis ossificans progressiva, 19,20 meaning a muscular inflammation that gradually turned into bones. However, this process affects not only muscles, but also soft parts such as articular capsules and ligaments.…”
Section: Epidemiology Of Fopmentioning
confidence: 99%
See 4 more Smart Citations
“…17,18 In 1918, Rosenstirn conducted an extensive review of the medical literature, describing 115 cases of FOP. 14,17 The disease was first named myositis ossificans progressiva, 19,20 meaning a muscular inflammation that gradually turned into bones. However, this process affects not only muscles, but also soft parts such as articular capsules and ligaments.…”
Section: Epidemiology Of Fopmentioning
confidence: 99%
“…26 Although most reports concern Caucasian patients, the disease affects all ethnic groups, with a predilection for males at a proportion of 4:1. 19,27 Since in most cases there is no family history, some studies have suggested that the disease is due to a sporadic mutation. 19 Some cases of FOP have been reported in the Brazilian medical literature.…”
Section: Epidemiology Of Fopmentioning
confidence: 99%
See 3 more Smart Citations